The Northern Ireland regional econometric model - Jefferson, Clifford W. (Statistical and Social Inquiry Society of Ireland, 1982)
Macroeconometric modelling of regional economies is in its infancy. While national models have been in widespread use in industrialised countries for many years, it is only comparatively recently that econometric models have been constructed for regions. National models with the national expenditure format have developed around a substantial body of economic theory together with the relevant national income statistics. The development of regional econometric models has been hindered by the relatively unsophisticated body of regional economic theory and the limited availability and quality of regional data. This paper outlines in general terms the structure of the Northern Ireland model. It follows the format of the more recent regional econometric models in the USA and is intended primarily for medium?term forecasting.
Symposium on Econometric Modelling
Read before the Society, 25 February 1982
Keywords: Econometric models of Northern Ireland economy; Macroeconometric modelling; Regional macroeconometric modelling; Medium term macroeconometric modelling; 314.15